Consultório na rua e o adoecer por tuberculose na população em situação de rua - Alecrim, Tatiana Ferraz de Araújo (Universidade Federal de São Carlos, 2022)
In São Paulo, there are around 31,884 homeless people, who are 48 to 67 times more susceptible to fall sick of tuberculosis (TB); 20.8% of those people restart treatment after having abandoned it. Given this scenario, the CnaR staff is presented as a care model that significantly contributes to the access of homeless population (HP) to healthcare services, widens the possibility of early diagnosis, treatment, monitoring and healing of the person with tuberculosis. This investigation had the general objective to analyze the evolution of the discourse of homeless people and the professionals of CnaR teams regarding tuberculosis in the city of São Paulo. It is a theoretical-methodological qualitative research based on French Discourse Analysis (DA) matrix premise. The participants of this study are professionals that compose the street clinic teams, and homeless people in treatment of tuberculosis in São Paulo city. A semi-structured script was used and the interviews were recorded on audio, fully transcribed and analyzed. This investigation was composed by 13 subjects, of them, 09 street clinic teams professionals and 04 homeless persons. The results come in four discoursive blocks, namely, living (survival) on the streets; the meaning of tuberculosis to homeless people, the meaning of tuberculosis to the professionals of street clinics; and mirrors: a path of hope. Homeless people are exposed to poverty, social deprivation, and a high risk of falling sick; these conditions create the daily need of adjustment, perceptions and strategies to their survival. The speeches of the professionals revealed the necessity of knowledge regarding the Brazilian’s SUS healthcare system, TB infection control protocols and manuals, understanding of the scenario, of teamwork and conjunction with social and health equipment. Furthermore, the study demonstrated the persistence on actions of continuous care and availability to establish bounds and recognize the homeless person as a citizen with rights. Homeless people revealed their strategies to street survival, the tuberculosis diagnosis being one of the tools to leave invisibility. The speeches revealed the difficulties faced on illness and treatment of TB, healing possibilities, the knowledge of the HP regarding the disease, the amount of importance of the bound created and the longitudinality of care to become important allies on the continued care. The conclusion is that the knowledge about the clinics, the therapeutics and the fluxes collaborate to the diagnosis and cure of TB; physical and emotional pain, as well as fear of death, are global feelings amongst the interviewed; the basic needs of daily life have a higher level of importance than the illness. The collateral effects of medicinal therapy increase the possibility to quit the treatment and the loneliness is a trace of homeless people. It was highlighted the importance of the completeness of care, beyond health scope, that the teamwork and work in chain are fundamental, that the care, the health awareness and education, the faith, and the bounds are necessary elements to care for homeless people with tuberculosis. It was also revealed that CnaR presents itself as a strategy of healthcare and social reintegration.
Consultório na rua and the coming down with tuberculosis in homeless population
Keywords: Equipes de consultório na rua; Tuberculose; População em situação de rua; Análise de discurso; Cuidado em saúde; Consultório na rua teams; Tuberculosis; Homeless population; Discourse analysis; Healthcare; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA